The matter of miracles : Neapolitan baroque architecture and sanctity - Hills, Helen (Rethinking art's histories., 2016)
This book investigates baroque architecture through the lens of San Gennaro's miraculously liquefying blood in Naples. This vantage point allows a bracing and thoroughly original rethink of the power of baroque relics and reliquaries. It shows how a focus on miracles produces original interpretations of architecture, sanctity and place which will engage architectural historians everywhere. The matter of the baroque miracle extends into a rigorous engagement with natural history, telluric philosophy, new materialism, theory and philosophy. The study will transform our understanding of baroque art and architecture, sanctity and Naples. Bristling with new archival materials and historical insights, this study lifts the baroque from its previous marginalisation to engage fiercely with materiality and potentiality and thus unleash baroque art and architecture as productive and transformational.